(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The structural properties, crystalline and clustering behavior of xNa2O·(1-x)TeO2 (15 £ x £ 65 mol% glasses have been investigated by FTIR spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM ). The experimental results have demonstrated that the basic structural units in telluride glasses change from highly strained TeO4 trigonal bipyramids to more regular TeO3 units containing non bridging oxygen atoms (NBO). The concentration of NBO atoms in telluride network increases with increasing? Na2O content. The present results suggest that (NBO) atoms in telluride glasses exist in their pure form in glasses of up to 35 mol% Na2O. But at higher Na2O concentrations, NBO atoms do not exist in their pure form; that is, the majority of NBO atoms are coordinated with high concentration from Na cations to form nano-crystalline clusters. The results based on X-ray diffraction (XRD), scanning electron microscopy (SEM) and differential scanning calomerty (DSC) reveal the presence of two crystalline phases: ? TeO2 and Na2Te4O9 phases during the crystallization process of the prepared glass in the region < 50 mol% Na2O. But at higher Na2O concentrations, Na2Te2O5 and NaTeO3 crystalline clustered phase in the nono size scale are the dominant type. This means that NBO in TeO3 trigonal pyramids will interact with the excess of Na cation resulting in the three-dimensional network containing nano size clusters particularly in telluride glasses containing 50 and 65 mol% Na2O. An increase in Na2O concentration in Na2O-rich telluride network results in increasing Na coordination instead of breaking more tellurium–oxygen bonds.